Biological synthesis of hybrid silver nanoparticles by Periploca aphylla Dcne. From nanotechnology to biotechnology applications - Arshad, Saba; Anwar, Natasha; Rauf, Mamoona; Anwar, Zeeshan; Shah, Mohib; Hamayun, Muhammad; Ud-Din, Jalal; Gul, Humaira; Nasim, Sahar; Lee, In-Jung; Arif, Muhammad (Frontiers in Chemistry, 2022)
Nanotechnology is one of the advanced technologies that have almost universal implications in every field of science. The importance is due to the unique properties of nanoparticles; however, green synthesized nanoparticles are considered eco-friendly. The current project was rationalized to prepare green-synthesized biogenic Periploca aphylla Dcne silver nanoparticles (Pe-AgNPs) and poly(ethylene glycol) methacrylate coated AgNPs nanocomposites (PEGMA-AgNPs) with higher potential for their application in plant tissue culture for enhancing the biomass of Stevia rebaudiana calli. The increased biomass accumulation (17.61 g/3 plates) was observed on a medium containing virgin Pe-AgNPs 40th days after incubation, while the maximum increase was found by supplementing virgin Pe-AgNPs and PEGMA capped AgNPs (19.56 g/3 plates), compared with control (12.01 g/3 plates). In this study, PEGMA capped AgNPs supplementation also induced the maximum increase in total phenolics content (2.46 mg GAE/g-FW), total flavonoids content (3.68 mg QE/g-FW), SOD activity (53.78 U/mL protein), GSH content (139.75 µg/g FW), antioxidant activity (54.3 mg AAE/g FW), FRAP (54 mg AAE/g FW), and DPPH (76.3 %) in Stevia rebaudiana calli compared with the control. It was concluded that virgin Pe-AgNPs and PEGMA capped AgNPs (hybrid polymer) are potent growth regulator agents and elicitors that can be exploited in the biotechnology field for growth promotion and induction of essential bioactive compounds and secondary metabolites from various commercially important and medicinally valuable plants such as Stevia rebaudiana without laborious field cultivation.